2017
DOI: 10.18203/2320-1770.ijrcog20173461
|View full text |Cite
|
Sign up to set email alerts
|

A study of various cesarean section techniques at a government tertiary care centre: Misgav Ladach cesarean section versus Pfannenstiel cesarean section

Abstract: Background: It is important to examine every step in any surgery to identify and evaluate its imortance, necessity and purpose with a view to find its better alternatives if they can be found at all. The most appropriate surgical procedure is the one which takes minimum time to be complete, simplest to perform, causing least damage and least complication for the patient. Present study was undertaken to assess the benefits of the Misgav Ladach cesarean section technique in comparison to the conventional Pfannen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Results of the quality assessment of all included studies are shown in Tables S1 and S2. All the randomised control trials judged via the RoB‐2 Tool were found to be of low risk, 10,19–30 or of some concern 31–38 . Similarly, all the observational studies judged via the ROBINS‐I Tool were found to be of low risk, 39–43 or of some concern 44 .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Results of the quality assessment of all included studies are shown in Tables S1 and S2. All the randomised control trials judged via the RoB‐2 Tool were found to be of low risk, 10,19–30 or of some concern 31–38 . Similarly, all the observational studies judged via the ROBINS‐I Tool were found to be of low risk, 39–43 or of some concern 44 .…”
Section: Resultsmentioning
confidence: 89%
“…The total number of patients that underwent CS were 15 251. Of these, 5809 (38.1%) underwent PKM, 10,19–44 3790 (24.9%) MLM, 21,23,25,27,30–32,34–36,38–41,43 and 5597 (36.7%) MMLM 10,19,20,22,24,26,28,29,33,36,42,44 . The range of means for ages of the entire maternal cohort was 23.16–32.33 years and the gestational cohort was 36.50–39.24 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations